Study of owner awareness and risk factors of feline obesity in Klang Valley - Misran, Nur Azlin (2016)
A cross-sectional questionnaire study of cat owners in Klang Valley was done in January 2016. In total 150 questionnaires were collected. The questionnaires comprised of three sections: demographics of the cat, feed and feeding regime and owner awareness and knowledge about feline obesity. The body condition score (BCS) of cats was rated by the cat owner using a validated five point scale. The objectives of this study are to determine the level of awareness of pet owner about the risk of obesity in cat and to determine factors that contributing obesity in cat. Data was analysed using descriptive statistics to identify the level of awareness of cat owner and rate of overweight and obesity cat involved in study. Overall, majority of the cat owner were aware about the risk of feline obesity (77%) and rate for overweight and obese cat was 47.4% (n=71). Based on the literature review, gender, neutering status, age, breed, management, number of cat in household, type of diet, frequency of feeding , amount of feed given, owner awareness about risk of obesity and owner knowledge about calorie needed for their cat were identify as potential to be a risk factor for feline obesity. Therefore, Chi square test was done to determine the association between those variables and chances of cat become overweight and obese (P < 0.05). In this study overweight and obese cats were more likely had relationship with neutering status, age of cat, type of diet, management and frequency of feeding. Then binary logistic regression conducted to find the major risk factor for feline obesity. Based on the results, cats that are neutered, senior age (> 9 years old), commercial diet, kept indoor and feeding more than three times a day have a high risk in developing obesity. This study highlighted the importance of owner attitude towards prevention of obesity as the cat owner knowledge about prevention of feline obesity is still low. Therefore owner education about feeding management and estimation of BCS is important to prevent the incidence of feline obesity.